A three-dimensional skull ontogeny in the bobcat (Lynx rufus) (Carnivora: Felidae): a comparison with other carnivores - Segura Gago, Alda Valentina (2015)
The maturation of mammalian carnivores from a lactating juvenile to a predatory adult requires a suite of changes in both morphology and behaviour. Bobcats (Lynx rufus (Schreber, 1777)) are medium-sized cats with well-developed skulls to process large prey that can exceed their body mass. An integrated view of the skull ontogeny in the bobcat was developed to detect the relationship between shape, size (on the basis of three-dimensional geometric morphometric analysis), and life history. Dietary changes from juvenile to adults were taken into account and compared with other carnivores. Newborns were different from the remaining age stages in the behavioral and morphological characters examined, which allows us to relate them to the terminal morphology reached during the prenatal period. All findings were related to the reinforcement of the skull and the enhancement of predatory skills in adult bobcats. The final cranial shape is reached in A2 age class, after 2 years of age, and once sexual maturity has been reached. This is a pattern not followed for the rest of carnivores previously studied, which might be related to the capacity of subduing prey that exceed them in size, a behavior not common in felids of the body size of bobcats.